Immune checkpoint therapy of mesothelioma: Pre-clinical bases and clinical evidences. (August 2017) - Calabrò, Luana; Ceresoli, Giovanni Luca; D'Incecco, Armida; Scherpereel, Arnaud; Aerts, Joachim; Maio, Michele
Highlights: No satisfactory treatment are current available for malignant mesothelioma patients. Several research lines are being pursued, among them, immunotherapy seems the most one promising approach in mesothelioma. The potential therapeutic role of targeting immune checkpoints used alone or in combination for mesothelioma is discussed. Abstract: Treatment with immune-checkpoint blocking monoclonal antibody (mAb) is demonstrating a significant efficacy in different tumor types. Here, we discuss the impact of this promising approach in malignant mesothelioma (MM), a still dreadful disease in which medical treatment has been set on platinum based chemotherapy for decades with unsatisfactory results.